Clinical, laboratory and coagulation system of blood feachers in patients with viral liver cirrhoses associated with virus hepatitis B, C and D - S. A. Bogushevich; K. I. Chuikova (Бюллетень сибирской медицины, 2009)
The research is devoted to study clinico-laboratory implications and indicators of coagulating system of blood at patiens with liver cirrhosis associated with virus hepatitises B, C and D. The group of 100 patients were analyzed. At patients combined the lesion of a liver viruses HCV and HBV met identical frequency with a HBV-infection (34%). The hepatocellular carcinoma is taped in 8% of cases. At 50 patients with a cirrhosis in subcompansation stage researches of coagulating system of blood have been carried out. According to the developed coagulogram consumption coagulopathy development became perceptible.